Kata Thinking management model as a tool to enhance continuous improvement capabilities in maintenance operations - Amaya González, Hernán Andrés; Rincón Cuta, Yeisson Alexis; Duarte Alarcón, Jennifer Astrid (Ingeniería Solidaria, 2024)
Introduction: This article is the result of a research project conducted by the Colombian Aerospace Force (FAC) during 2022 and 2023 as part of its ongoing pursuit of cutting-edge knowledge management. The study focuses on improving its management model, contributing to the continuous enhancement of maintenance in the aeronautical sector.Problem: Lessons Learned, as a tool for preventing unwanted events, has been widely discussed due to the high recurrence of such events. This recurrence indicates that Lessons Learned are not being effectively utilized.Objective: This document establishes a baseline aimed at strengthening organizational performance by integrating Toyota Kata principles into the Lessons Learned methodology.Methodology: The integration of the Kata model with the Lessons Learned methodology was conducted by identifying common elements. This integration was then implemented using the Improvement Kata and the Coaching Kata.Results: The study found that the Lessons Learned process consists of three stages that align with the stages of the Kata model. Additionally, a pattern of recurring Lessons Learned was identified in three key areas. Based on these findings, an application guide for the Kata-Lessons Learned model was developed to address these recurrences.Conclusion: The proposed baseline enables the effective application of the Kata model within the Lessons Learned methodology. The future adoption of this integrated model will contribute to the continuous improvement of the industry.Originality: This research provides practical guidance on incorporating a modern management model into the maintenance sector.Limitations: The Kata-Lessons Learned model must be tested in operational settings to validate its effectiveness.